Effect of Amniotic Membrane/Collagen-Based Scaffolds on the Chondrogenic Differentiation of Adipose-Derived Stem Cells and Cartilage Repair - Cao, Le; Tong, Yuling; Wang, Xiao; Zhang, Qiang; Qi, Yiying; Zhou, Chenhe; Yu, Xinning; Wu, Yongping; Miao, Xudong (Frontiers in Cell and Developmental Biology, 2021)
Objectives: Repairing of articular cartilage damage is challenging. Clinically, tissue engineering technology is used to induce stem cell differentiation and proliferation on biological scaffolds to repair defective joints. However, no ideal biological scaffold has been identified. This study investigated the effects of amniotic membrane/collagen scaffold on the differentiation of adipose-derived stem cells (ADSCs) and articular cartilage repair. Methods: Adipose tissue of New Zealand rabbits was excised, and ADSCs were isolated and induced for differentiation . An articular cartilage defect model was constructed to identify the effect of amniotic membrane/collagen scaffolding on cartilage repair. Cartilage formation was analyzed by imaging and toluene blue staining. Knee joint recovery in rabbits was examined using hematoxylin and eosin, toluidine, safranine, and immunohistochemistry at 12 weeks post-operation. Gene expression was examined using Elisa, RT-PCR, western blotting, and immunofluorescence. Results: The adipose tissue was effectively differentiated into ADSCs, which further differentiated into chondrogenic, osteogenic, and lipogenic lineages after three weeks' culture in vitro. Compared with platelet-rich plasmon (PRP) scaffold, the amniotic membrane scaffold better promoted the growth and differentiation of ADSCs. Additionally, scaffolds containing the PRP and amniotic membrane efficiently enhanced the osteogenic differentiation of ADSCs. The levels of COL1A1, COL2A1, COL10A1, SOX9 and ACAN in ADSCs + amniotic membrane + PRP group were significantly higher than the other groups both in vitro and in vivo. The Wakitani scores of the ADSC + amniotic membrane + PRP group were lower than that in ADSC + PRP (4.4 ± 0.44**), ADSC + amniotic membrane (2.63±0.38**), and control groups (6.733±0.21) at week 12 post-operation. Osteogenesis in rabbits of the ADSC + amniotic membrane + PRP group was significantly upregulated when compared with other groups. Amniotic membranes significantly promoted the expression of cartilage regeneration related factors (SOX6, SOX9, RUNX2, NKX3-2, MEF2C, and GATA4). The ADSC + PRP + amniotic membrane group exhibited the highest levels of TGF-β, PDGF and FGF while exhibited the loweset level of IL-1β, IL6, and TNF-αin articular cavity. Conclusion: Amniotic membrane/collagen combination-based scaffolds promoted the proliferation and cartilage differentiation of ADSCs, and may provide a new treatment paradigm for patients with cartilage injury.